Diseño y construcción de una máquina para rallar coco - Palacios Mendoza, Javier Alejandro (2016)
Actually in Esmeraldas city to grate coconut is very rustic, so people when sell the differents products of the coconut they need doing hard physical effort for to get grate it and people last a lot of time in its carrying. Previously the coconut do not had higher incidence in the community, only because it was used for to make foods and for the carrying “cocadas” low percents, but actually the coconut is a fruit very seller for the products deriving of the fruit. The coconut is used for to make cocadas and there are a lot of people in Esmeraldas city who make cocadas. This project include the properties, the benefits which has the coconut in alimentary and medicinal place considering this fruit as a products very consumed around the world as this knowed in the rest of the history. The partnerships of the traders don’t have a machine which to let grate a great quantity of coconut with the demand that this generates, people need to find differents kinds of the national and international machines which let to them optimize the products. For this reason the best alternative of the machines and is elaborated the same that is adapted to the requirements of the differents markets, reducing costs, increasing production and doing easy the operator work. With the machine which is constructed is increasing production of the grated of the coconut in 271% which it ensures the total growth for people dedicate to this business.